Phylogenetic analysis and reconfiguration of genera in the cestode order Diphyllidea - Caira, Janine N. (2013)
The generic boundaries of the Diphyllidea are reassessed based on parsimony and likelihood phylogenetic analyses of 28S rDNA (ribonucleic acid large subunit), 18S rDNA (ribonucleic acid small subunit), and COI (cytochrome oxidase subunit I) sequence data for 31 species representing morphological variation across the order. Trees resulting from these analyses yielded a number of well-supported clades that are congruent with unique morphological features mandating generic revision of the order and erection of at least two new genera. Species originally assigned to Echinobothrium van Beneden, 1849 but bearing a corona of spines on the region of the scolex anterior to the bothria and posterior to the apical organ armature are transferred to Coronocestus n. gen.; members of this genus typically parasitize triakid sharks, although one report from a hemiscylliid shark exists. Species with lateral hooklets arranged in continuous bands, rather than in two distinct clusters, are transferred to Halysioncum n. gen.; all species parasitize batoids, mostly myliobatids and rhinopterids, but a few records also exist from arhynchobatids, rhinobatids, platyrhinids and urotrygonids. Our analyses support transfer of the five species originally assigned to Macrobothridium Khalil and Abdul-Salam, 1989 owing to their lack of cephalic peduncle spines to Echinobothrium. As a consequence, Echinobothrium sensu stricto includes species both with and without spines on the cephalic peduncle, but all members of the genus possess lateral hooklets arranged in clusters on either side of the dorsal and ventral apical hooks. With respect to diphyllideans parasitizing catsharks, Ahamulina Marques, Jensen and Caira, 2012 is unique in possessing apical hooks but lacking lateral hooklets and Ditrachybothridium Rees, 1959 is unique in entirely lacking scolex armature. By far the majority of species of Echinobothrium sensu stricto parasitize skates of the family Rajidae, guitarfish of the family Rhinobatidae, and stingrays of the dasyatid genera Taeniura Müller and Henle, Dasyatis Rafinesque, and Himantura Müller and Henle, although a single species each has been reported from Anacanthobatidae, Rhynchobatidae, Platyrhinidae and Myliobatidae. It now seems clear that while by far the majority of diphyllideans parasitize batoids, the diphyllideans parasitizing sharks, and catsharks in particular, remain problematic. Additional collections from these carcharhiniform hosts are likely to be particularly illuminating.